Real-world challenge for clinicians treating advanced gastroesophageal adenocarcinoma (Review) - Baxter, Mark A. (Int J Oncol, 2021)
Gastroesophageal adenocarcinoma (GOA) is a disease of older people. Incidence is rising in the developed world and the majority of patients present with advanced disease. Based on clinical trial data, systemic chemotherapy in the advanced setting is associated with improvements in quality of life and survival. However, there is a recognised mismatch between trial populations and the patients encountered in clinical practice in terms of age, comorbidity and fitness. Appropriate patient selection is essential to safely deliver effective treatment. In this narrative review, we discuss the challenges faced by clinicians when assessing real-world patients with advanced GOA for systemic therapy. We also highlight the importance of frailty screening and the current available evidence we can use to guide our management.